DUAL FACTOR THEORY OF JOB SATISFACTION: A REPLICATION IN LEATHER INDUSTRY IN TAMIL NADU - Thirupathy, A. (International Journal of Research -GRANTHAALAYAH, 2016)
As Frederick Herzberg noted in his 1968 article, “what has been unraveled [about the psychology of motivation] with any degree of assurance is small indeed. Herzberg believed that organizations have only limited power to motivate employees. Managers should make sure their incentive systems function reasonably well but should concentrate on enriching the work. There are down to earth managers who shout, “Kick the person!” And this type of manager is right. The surest and least difficult way of getting someone to do something is to administer a kick in the pants - to give what might be called the KITA(Kick in ask). This opened up the field of communications, a new area of “scientifically” sanctioned KITA.